Peranan Akuntansi Pertanggungjawaban dalam Rangka Penilaian Kinerja Pusat Biaya pada Departemen Produksi PT. “X” di Surabaya - Diana Zuhroh (AKUNTANSI 45, 2024)
This study discusses the role of accountability accounting in the context of assessing the performance of the cost center at production departementat PT "X" by using a qualitative research approach with a qualitative descriptive method. The data analysis technique used is by comparing the production cost budget with its realization. The results of the study show that in the cost classification, PT "X" has not separated between controlled costs and uncontrolled costs, besides that the part under the production committee, starting from the material preparation part, the forming part, and the finishing part have also not been involved in the process of preparing the production cost budget. With the accountability report, management can measure the efficiency and effectiveness of production costs. So that PT "X" no longer has difficulty in determining which parts of the inefficiency occur, so that it can help management in decision-making and improve the company's overall performance.